COVID-19 and lockdown: Insights from Mumbai - Kanchan Mukherjee (Wolters Kluwer Medknow Publications, 2020)
Background: Mumbai is facing the full brunt of the COVID-19 pandemic epidemiologically and economically. Objectives: The objective was to understand the spatial distribution and trends of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) in Mumbai during the lockdown period and draw insights for effective actions. Methods: Spatial and trend analysis was conducted to trace the spread of the virus during the lockdown period in April 2020. The administrative divisions of Mumbai, in the form of wards and zones, have been used as units of analysis. Results: Greater Mumbai area occupies only 0.015% of the landmass of India, but is contributing to over 20% of the SARS-CoV-2 cases in India. Cases of SARS-CoV-2 infections have increased over 375 times within 50 days of the lockdown. An analysis of trends across the wards during the 3-week period (April 4 to April 25) shows a skewed pattern, with three zones out of six contributing to the vast majority of cases in Mumbai. The wards with higher formal economic activity are relatively less affected than the other wards. The test positivity rate in Mumbai is much higher than the rest of India. Conclusion: The study suggests that the virus had already spread to the community in Mumbai before the lockdown started.